2014
DOI: 10.1002/2014gl060107
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric response to the shock and acoustic waves excited by the launch of the Shenzhou 10 spacecraft

Abstract: We used a dense GPS network in China to track the ionospheric response to waves excited by the launch of the rocket that carried Shenzhou 10 spacecraft on 11 June 2013. The long-distance propagation of shock and acoustic waves were observed on both sides of the rocket's trajectory. On the southern side, the wave structures (characterized by a horizontal extension of~1400 km and initial amplitudes of 0.3 total electron content unit (TECU) and 0.1 TECU for the shock and acoustic waves, respectively), traveled so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 35 publications
2
56
0
1
Order By: Relevance
“…This may be because the dissipation of the TID's amplitude limits its propagation range. Although the dissipation of amplitude of the first TID cannot be directly observed because of the limited number of stations in the near-field of the blast site, strong dissipation of shock waves excited by other sources, such as rocket launches, has previously been addressed (Ding et al, 2014).…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because the dissipation of the TID's amplitude limits its propagation range. Although the dissipation of amplitude of the first TID cannot be directly observed because of the limited number of stations in the near-field of the blast site, strong dissipation of shock waves excited by other sources, such as rocket launches, has previously been addressed (Ding et al, 2014).…”
Section: Observationsmentioning
confidence: 99%
“…Nuclear explosions that were detonated as weapons tests took place mainly in the 1950s and 1960s before the Partial Nuclear Test Ban Treaty was signed. During those years, atmospheric and ionospheric disturbances that were possibly excited by these explosions were studied extensively through observations of globally distributed microbarographs and ionosondes, respectively (Yamamoto, 1954;Donn and Ewing, 1962;Wickersham, 1966). As meteorite blasts happen only rarely, it is most convenient to compare our results with those early observations in the context of possible propagation mechanisms of the ionospheric disturbances.…”
Section: Comparison Of Tids Excited By the Meteorite Blast With Tids mentioning
confidence: 99%
See 1 more Smart Citation
“…GPS network observations of natural hazard-related TEC perturbations reveal unprecedented detail into the spatial structure of wave fields and responses and have indicated that observed signatures are more pronounced in the magnetic equatorward direction from the source. This feature has been present in connection with a wide range of physical sources including, for example, volcanoes [Heki, 2006], weather events [Nishioka et al, 2013], earthquakes [Heki and Ping, 2005;Saito et al, 2011], and even rocket launches [Ding et al, 2014]. It has been proposed that this feature of the TEC perturbations is related to the local magnetic field geometry [Heki and Ping, 2005;Shinagawa et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…They further modeled the acoustic wave with periods of 3.3-6.6 min and with the phase speed of ∼ 716 m s −1 by ray tracing method. Ding et al (2014) used a dense GPS network in China to observe the shock and acoustic waves generated during the launch of the Shenzhou-10 spacecraft. Long-distance propagation shock and acoustic waves were observed appearing on both sides of the rocket's trajectory with different amplitude of perturbations.…”
Section: Introductionmentioning
confidence: 99%